2008
DOI: 10.1016/j.febslet.2008.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a chromosomal toxin–antitoxin system in Mycobacterium tuberculosis

Abstract: In the present paper, we report the biochemical characterization of a chromosomal toxin-antitoxin (TA) system in Mycobacterium tuberculosis, consisting of the Rv1991c gene and its upstream open reading frame (ORF) termed Rv1991a. Rv1991c was characterized as a toxin with ribonuclease activity and Rv1991a as the antitoxin against Rv1991c. Rv1991a interacted with Rv1991c to form a complex. A promoter located immediately upstream of Rv1991a was identified. Both Rv1991a and the Rv1991a-Rv1991c complex were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
(22 reference statements)
2
16
0
Order By: Relevance
“…In addition, there is a possibility that MazF toxin in complex with their cognate antitoxin can regulate transcription from their own promoter as reported in the case of MazEF6 (ref. 51). To establish a successful infection, Mtb must adapt to acidic, nitrosative, oxidative, nutrient-limiting and low-oxygen conditions encountered in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a possibility that MazF toxin in complex with their cognate antitoxin can regulate transcription from their own promoter as reported in the case of MazEF6 (ref. 51). To establish a successful infection, Mtb must adapt to acidic, nitrosative, oxidative, nutrient-limiting and low-oxygen conditions encountered in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of MazF homologue Rv1991c inhibited the growth of M. smegmatis, which was moderately reversed after expression of its cognate antitoxin, Rv1991a (51). Mechanistically, M. tuberculosis MazF-mt3 and MazF-mt7 act as endoribonucleases, targeting the unique sequences CUĈ CU/UUĈ CU (MazF-mt3) and UĈ GCU (MazF-mt7) in single-stranded RNA (52).…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, 30 out of 38 putative TA systems from M. tuberculosis were functional when expressed in E. coli (61). Of the nine MazF homologs identified in M. tuberculosis, seven have been studied and shown to cause growth arrest when expressed in E. coli (49,62,63 (64,65). Further worked showed that expression of the RelE2 toxin in M. tuberculosis induced the formation of drug-specific persisters in vitro; however, deletion of relE2 did not affect the level of persisters of M. tuberculosis in rifampin-treated mice ruling out a role for relE2 in the generation of bacilli that survive multidrug therapy (66).…”
Section: Discussionmentioning
confidence: 99%